2022
DOI: 10.15174/au.2022.3189
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception about the covid-19 pandemic and its effect on self-medication practices in population of northwestern Mexico

Abstract: The objective of the present study was to analyze the effect of the risk perception of covid-19 on self-medication practices in Mexican population. A total of 526 participants over 18 years of age were surveyed, 68.4% women and 31.6% men residing in northwestern Mexico. Using a structural model, the relation and prevalence of self-medication were analyzed. Risk perception about covid-19, consisting of preventive practices and the perception of the threat of the pandemic, was negatively correlated with self-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Based on psychometric models of health and crisis communication, existing studies have found publics' increased perception of their level of involvement to be an important factor influencing such communicative behaviors [30]. As personal involvement with COVID-19 was perceived or expected to be high, people would become increasingly concerned about treatment and medication information and resources [31,32].…”
Section: Topics About Personal Vs Social Risk Of Covid-19 Medication ...mentioning
confidence: 99%
“…Based on psychometric models of health and crisis communication, existing studies have found publics' increased perception of their level of involvement to be an important factor influencing such communicative behaviors [30]. As personal involvement with COVID-19 was perceived or expected to be high, people would become increasingly concerned about treatment and medication information and resources [31,32].…”
Section: Topics About Personal Vs Social Risk Of Covid-19 Medication ...mentioning
confidence: 99%